ON THE LANGUAGE STYLE OF THE LAW - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The paper examines the language style of modern laws and the relevance of the language for the law and lawyers in general.In the first part of the paper the author points to the importance of the phenomenon of language and the relevance of the study thereof. Later it gives arguments that support the position that the language is of a great importance both for the law and for the lawyers.In the central part of the paper the author discusses the language style used in laws and maintains that the language style of the modern European laws is to a great degree influenced by the nature and character of such laws, as well as by the nature of the subject matter of the laws, goals that such laws are to achieve and  by a desire to achieve 'positivism' in law.In the end, the author stresses that today we have laws that are not only written in rough language but are also of poor content which paints a "gloomy picture of the language quality of our laws". In order to change such situation, the author points to the necessity of more profound knowledge of the language and linguistics by the lawyers.
Keywords: language style of the law; language of the law; language and law; language